ANALYTICAL EXERCISE FROM THE READERS’ POINT OF VIEW REGARDING THE SERVICES AND FACILITIES PROVIDED TO THE READERS IN COLLEGE LIBRARIES” IN THE CONTEXT OF NAGPUR UNIVERSITY - S. gedam, Tushar; Borkar, Vikas S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sadar Abhyas Rashtrasant Tukdoji Maharaj Nagpur Vidyapeeth Nagpur attached aided Arts, Commerce and Science College’s library has made efforts to provide analytical practice from the readers’ point of view regarding the services and facilities provided. The college library makes every effort to improve the services and facilities of its library by the readers and for this, the college library is seen making efforts from time to time to improve its services and facilities.